Impact of SWCNT processing on nanotube-silicon heterojunctions. Issue 15 (24th March 2016) - Harris, John M.; Headrick, Robert J.; Semler, Matthew R.; Fagan, Jeffrey A.; Pasquali, Matteo; Hobbie, Erik K.
Abstract : We use a variety of processing approaches to fabricate heterojunctions of single-wall carbon nanotubes (SWCNTs) and silicon. Using both unsorted and chirality-enriched SWCNTs processed in super-acid solvents, we quantify the influence of SWCNT purity, alignment and doping on device performance. Abstract : Single-wall carbon nanotube (SWCNT) films are ideal components for thin, flexible, and durable electronic devices. Here, we use a variety of processing approaches to fabricate SWCNT-silicon heterojunctions from both unsorted and chirality-enriched SWCNTs. Through measured structure/processing/property relationships, we quantify the influence of SWCNT purity, alignment and residual doping on device performance and diode characteristics. Our results show that mixed-type unaligned SWCNTs processed in super-acid solvents can achieve state-of-the-art performance. The devices perform comparably to those fabricated from type or chiral-purified SWCNTs, despite what appear to be significant deviations from ideal diode behavior. Our results clarify a direct route for processing nanotube-silicon heterojunctions while providing additional insight into the underlying nature of these devices.